Allergic sensitization to pegylated interferon‐α results in drug eruptions - Meller, S.; Gerber, P. A.; Kislat, A.; Hevezi, P.; Göbel, T.; Wiesner, U.; Kellermann, S.; Bünemann, E.; Zlotnik, A.; Häussinger, D.; Erhardt, A.; Homey, B. (Allergy (Copenhagen), 2015)
Background The introduction of pegylated interferon (PEG‐IFN)‐α in the treatment of chronic hepatitis C has led to an increase in sustained virological response. Despite reduced immunogenicity of the pegylated form in comparison with native interferon (IFN)‐α, a high frequency of adverse cutaneous reactions has been reported with pegylated IFN‐α. Here, we aimed to investigate the immunological mechanisms underlying pegylated IFN‐α‐induced drug eruptions. Methods Hepatitis C patients suffering from drug eruptions in association with administration of pegylated interferons were enrolled in the study (n = 22). Subjects were tested for sensitivity to pegylated IFN‐α2a, pegylated IFN‐α2b, or ribavirin using intradermal, scratch, and/or patch tests, as well as lymphocyte activation tests (LATs). Skin biopsies obtained from pegylated IFN‐α‐associated exanthemas, as well as from localized inflammatory skin reactions at pegylated IFN‐α injection sites, were analyzed for the expression of relevant chemokines by quantitative real‐time PCR and immunohistochemistry. Results A subset of patients suffering from pegylated IFN‐α‐associated exanthemas displayed positive intradermal tests to PEG‐IFNs but not to conventional IFN (11/22). In selected patients, this observation correlated with the presence of pegylated IFN‐specific T cells (3/11). Chemokine profiles of inflammatory skin reactions at the injection sites reflected an IFN‐α‐signature, whereas lesional skin of exanthemas showed induction of TH2‐associated chemokines. Conclusions Our results indicate that specific sensitizations are one cause of exanthemas under therapy with PEG‐IFNs. Clinical proof‐of‐concept analyses demonstrate that affected patients may benefit from a switch to conventional, nonpegylated drugs, enabling IFN‐α therapy continuation without drug‐associated skin eruptions.